2009
DOI: 10.1007/s11240-009-9529-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamines on in vitro somatic embryogenesis in Momordica charantia L.

Abstract: The effects of exogenous polyamines (PAs) on enhancement of somatic embryogenic calli was investigated in Momordica charantia L. in vitro. Induction of somatic embryogenesis (SE) in leaf explants of M. charantia after 21 days of culture in Murashige and Skoog (MS) medium was determined using scanning electron microscopy. During induction of SE there were high titers of Putrescine (Put) as compared to Spermidine (Spd) and Spermine (Spm), a prerequisite for cell division. Addition of PAs to the embryogenic media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…Similar results were also reported by Dewi et al (2001) and Dewi and Purwoko (2008). Paul et al (2009) studied the influence of putrescine (0.1, 0.5, and 1 mM), spermidine (0.1, 0.5, and 1 µM), and spermine (0.1, 0.5, and 1 µM) on somatic embryogenesis in M. charantia L. and found that 1 mM putrescine concentration was the most effective in terms of somatic embryogenesis, followed by 0.1 µM concentration of spermine and spermidine, which also supports our findings. The results of both studies showed that spermine and spermidine should be used in much lower doses than putrescine to enhance somatic embryogenesis and plant regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also reported by Dewi et al (2001) and Dewi and Purwoko (2008). Paul et al (2009) studied the influence of putrescine (0.1, 0.5, and 1 mM), spermidine (0.1, 0.5, and 1 µM), and spermine (0.1, 0.5, and 1 µM) on somatic embryogenesis in M. charantia L. and found that 1 mM putrescine concentration was the most effective in terms of somatic embryogenesis, followed by 0.1 µM concentration of spermine and spermidine, which also supports our findings. The results of both studies showed that spermine and spermidine should be used in much lower doses than putrescine to enhance somatic embryogenesis and plant regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…The addition of PAs favored embryogenic responses in different species (Ahmadi et al, 2014;Kevers et al, 2000;Paul et al, 2009;Steiner et al, 2007;Yadav and Rajam, 1998). In Hevea brasiliensis, the addition of PAs increased the amount of embryogenic callus and the number of embryos per gram of callus using 50 µM Spd (El-Hadrami et al, 1989a, b) and also in Brassica napus the addition of 2.5 µM Put for 48 h increased three-fold the embryo formation and 5.56 µM Put increased fourfold the embryo conversion (Ahmadi et al, 2014).…”
Section: Effect Of Polyamines On the Efficiency And Developmental Mormentioning
confidence: 99%
“…In another report, Paul et al ( 2009 ) investigated the effect of various polyamines (PA) on somatic embryo induction in M. charantia . Somatic embryos were induced from leaf explants on MS medium supplemented with 2.7 μM NAA and 22.0 μM BA after 21 days of culture.…”
Section: Somatic Embryogenesismentioning
confidence: 99%